TOURISM CIRCULARITY AND VALUE CREATION: A BRAND-NEW OFFERINGS FROM TOURISM DESTINATION IN INDONESIA - Sijabat, Ferdi Nazirun; Nurbismi, Nurbismi; Maulida, Zenitha; Yunidar, Syafira (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
This article aims to overview the opportunity to deliver a brand-new offering from tourism destination that is tourism circularity. Whereby, destination management organization might set a purposeful goal of making destination leaner toward generating circular value creation from each industrial players and stakeholders. Besides, the circularity value of tourism may also contribute to reducing waste and lasting the use of resources within tourism and hospitality industry.  Literature review was used as a method by collecting articles relating to tourism and circular economy and value creation to enable to develop a solid understanding on its relationship. This article is to contribute to the extension of discourses and implementation of circular economy value creation for tourism destination in Indonesia. An adopted model of stakeholder value creation and tourism circular economy were developed in a way to produce a brand-new offering.